IMPLEMENTATION OF ZAKAT REDUCTION POLICY FOR STATE CIVIL SERVANTS BASED ON THE REGULATION OF THE MAYOR OF LHOKSEUMAWE NUMBER 33 OF 2017 CONCERNING THE MAMAGEMENT MECHANISM OF ZAKAT, INFAQ, SHADAQAH AND WAQAF - Amru Alba; Fidhia Aruni; Rudi Kurniawan; Muhammad Muhammad (Universitas Galuh, 2021)
The implementation of the Zakat Reduction Policy for State Civil Servants (ASN) based on the Regulation of the Mayor of Lhokseumawe Number 33 of 2017 concerning the Zakat Management Mechanism